Sedimentary and geochemical characterization of the sediments of the Boca Paila Lagoon system, Yucatan Peninsula, Mexico - Guadarrama-Guzmán, P.; Sujitha, S.B.; Jonathan, M.P.; Roy, P.D.; Nagarajan, Nagarajan; Rodríguez-Espinosa, P.F.; Mendoza, L.A.; Campos Villegas, L.E. (2025)
In this paper, we investigated the Boca Paila lagoon system that comprises the Campechen (CP), Boca Paila (BP) and San Martin (SM) lagoons along the eastern coast of the Yucatan Peninsula, Mexico to document the distribution and provenance of sediments. Henceforth, forty-one surface sediment samples were collected to analyze the geochemical, petrographical, carbonate content, magnetic susceptibility, and textural parameters. The average concentration of sand was found to be 88.26 % (BP), 81.64 % (CP), and 89.47 % (SM), depicting the fact that sand predominates in shallow water bodies with moderate to high energy environments. Petrography results revealed that the sediments majorly contained micritized bioclasts and calcite crystals formed from the recrystallization of carbonate mud or the direct precipitation of calcite in quiet water environment with minimal mud winnowing within the deposition basin. The major and trace element geochemistry revealed high concentrations of Ca (33.01 %), Mg (1.33 %), and Sr (3493.51 ppm) and the mineralogy was mainly composed of calcite and aragonite. In this study, trace element concentrations followed an order of (all values in ppm): Sr (3493.51) < Rb (13.12) < U (9.49) < Y (4.91) < Cd (2.5) and Mo (2.3). Likewise, elemental ratios (Ti/K, Sr/Ca, Fe/Ca, Ca/S) indicated the biogenic origin of the sediments with low inputs of terrigenous continental weathering. Although the sand grains are predominantly limestone, they are transported from shorter distances and are chemically less mature. This study enhances our comprehension of the lagoon system and offers crucial data for geochemical surveys in regions with similar geological features.